The diagnostic value of lipoprotein-related phospholipase A2 and matrix metalloproteinase-9 in identifying patients with coronary plaque or stenosis - Sungur Neslihan; Muhtaroğlu Sabahattin; Keti Didem Barlak; Imamoğlu Hakan (Romanian Journal of Laboratory Medicine)
Coronary computed tomography angiography (CCTA) is the gold standard method for detecting the presence of coronary plaque and stenosis in atherosclerosis. However, the nephrotoxic effects of contrast agents applied during angiography and the adverse effects of radiation are known. Alternative diagnostic tools are always needed to evaluate coronary arteries. Therefore, combining the results of CCTA with Lipoprotein-associated phospholipase A2 (Lp-PLA2) and Matrix metalloproteinase (MMP)-9, which are thought to be associated with atherosclerotic plaque, may reduce cardiovascular events in patients with suspected atherosclerosis.